2010
DOI: 10.1016/j.jbi.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Validating pathophysiological models of aging using clinical electronic medical records

Abstract: Bioinformatics methods that leverage the vast amounts of clinical data promises to provide insights into underlying molecular mechanisms that help explain human physiological processes. One of these processes is adolescent development. The utility of predictive aging models generated from cross-sectional cohorts and their applicability to separate populations, including the clinical population, has yet to be completely explored. In order to address this, we built regression models predictive of adolescent chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For instance, DeepPatient uses denoising Autoencoder (dAE) to perform unsupervised feature extraction from EMR [21]. Most relevant to the work presented here is a study that implemented a Least Angle Regression (LARS) model to predict the age of adolescents using 39 biomarkers from a blood test [5]. The model identified alkaline phosphatase and creatinine levels as the most predictive biomarkers for both male and female age; hematocrit and mean-cell-volume levels were found to be the most predictive markers for males, whereas total serum globulin was the most predictive marker for females.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, DeepPatient uses denoising Autoencoder (dAE) to perform unsupervised feature extraction from EMR [21]. Most relevant to the work presented here is a study that implemented a Least Angle Regression (LARS) model to predict the age of adolescents using 39 biomarkers from a blood test [5]. The model identified alkaline phosphatase and creatinine levels as the most predictive biomarkers for both male and female age; hematocrit and mean-cell-volume levels were found to be the most predictive markers for males, whereas total serum globulin was the most predictive marker for females.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated the utility for patient clinical biomarker vectors, which we termed clinarrays, in distinguishing between different severities of disease [ 7 ]; in integrative analysis with gene expression measurements to elucidate genes related to maturation and aging [ 8 ]; and to build a model of pediatric aging [ 9 ]. Clinarrays are a vector representation of a person’s physiological biomarker state across all visits at a hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In this special issue, D. Chen et al present customary molecular clinical measurements - such as creatinine and alkaline phosphatase - as new predictive biomarkers for aging[3]. These regression models, conducted for chronological ages of adolescents in the 2001-2002 National Health and Nutrition Examination Survey (NHANES) datasets [4] and validated using the 2003-2004 data, satisfactorily match the results seen in the aging process using cohorts collected from a hospital-based electronic health record system, and holds the potential to identify adolescent development-related disorders.…”
mentioning
confidence: 99%